2015
DOI: 10.1063/1.4917185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phase transformation on the microstructures and magnetostriction of Fe-Ga and Fe-Ga-Zn ferromagnetic shape memory alloys

Abstract: The phase transformation and magnetostriction of bulk Fe 73 Ga 27 and Fe 73 Ga 18 Zn 9 (at. %) ferromagnetic shape memory alloys (FSMs) were investigated by transmission electron microscopy (TEM), x-ray diffraction (XRD), and a magnetostrictive-meter setup. For the Fe 73 Ga 27 FSM alloy solution treated at 1100 C for 4 h and quenched in ice brine, the antiphase boundary segments of the D0 3 domain were observed in the A2 (disordered) matrix, and the Fe 73 Ga 27 FSM alloy had an optimal magnetostriction (k k s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Anelastic effects for phase transitions at higher temperatures have as yet not been reported in the literature. Doping Fe-Ga with rare earth elements enhances magnetostriction in Fe- (17)(18)(19)Ga alloys by creating local inhomogeneities [9][10][11] and stabilizes the metastable bcc-derivative phase in as cast Fe-27Ga alloys by preventing L1 2 phase nucleation on the D0 3 grain boundaries 7,[12][13][14] . The structure of metastable Fe-27Ga type alloys before their transition to equilibrium L1 2 phase may show several metastable phases (A2, B2, D0 3 ), the size of which, as reported in the literature, can be from nano (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Anelastic effects for phase transitions at higher temperatures have as yet not been reported in the literature. Doping Fe-Ga with rare earth elements enhances magnetostriction in Fe- (17)(18)(19)Ga alloys by creating local inhomogeneities [9][10][11] and stabilizes the metastable bcc-derivative phase in as cast Fe-27Ga alloys by preventing L1 2 phase nucleation on the D0 3 grain boundaries 7,[12][13][14] . The structure of metastable Fe-27Ga type alloys before their transition to equilibrium L1 2 phase may show several metastable phases (A2, B2, D0 3 ), the size of which, as reported in the literature, can be from nano (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The Dy content seems to blend with the Fe-Ga alloys, which improves the microstructural properties [30]. The existence of D0 3 and L1 2 phases along with the A2 phase is confirmed by the excess of grain size.…”
Section: Optical Microscopymentioning
confidence: 80%
“…Gao et al [19] found that adding Cr to polycrystalline Fe-Ga alloy can significantly improve the mechanical properties at room temperature, while the magnetostrictive coefficient is only 70ppm. If Fe73Ga18Zn9 is prepared by adding 9% Zn into fe73ga27 alloy, after quenching and aging at 700 ℃ for 24 hours, it can improve the magnetostrictive property and maintain stability, and improve the ferromagnetic shape memory effect, which provides the possibility for the application of the alloy in high-temperature environment [20].…”
Section: D 4d Transition Elementsmentioning
confidence: 99%